Upland rice In Africa: a guide for farming techniques - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Upland rice Macmillan (The Tropical Agriculturalist) a French series of practical field guides and textbooks